2013
DOI: 10.1002/imhj.21423
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status Affects Oral and Manual Exploration Across the First Year

Abstract: Oral and manual exploration are part of the foundation of problem solving and cognition in infancy. How these develop in an at-risk population, infants in poverty, is unknown. The current study tested exploratory behaviors longitudinally at 6, 9, and 12 months in infants from high- and low-socioeconomic (SES) families. Oral exploration consisted of passive and active mouthing and looks after active mouthing. Manual exploration consisted of frequency of fingering, rotating, and transferring the object. High-SES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 40 publications
1
16
1
Order By: Relevance
“…For surface exploration, low‐SES infants rubbed more, especially on the flexible surface. This was contrary to our hypotheses given that low‐SES infants generally show less exploration (Clearfield et al, ). Although the low‐SES infants demonstrated selectivity in rubbing the surface, rubbing the flexible surface may not be as conducive to learning about the surface as all of the other possible surface behaviours (pressing, picking and banging).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…For surface exploration, low‐SES infants rubbed more, especially on the flexible surface. This was contrary to our hypotheses given that low‐SES infants generally show less exploration (Clearfield et al, ). Although the low‐SES infants demonstrated selectivity in rubbing the surface, rubbing the flexible surface may not be as conducive to learning about the surface as all of the other possible surface behaviours (pressing, picking and banging).…”
Section: Discussioncontrasting
confidence: 99%
“…These infants show deficits in attention by 6 months and in the developmental trajectory of cognitive flexibility (Clearfield & Jedd, ; Lipina et al, ). Most relevant, low‐SES infants explored less and used less sophisticated exploratory behaviours than high‐SES infants by 12 months (Clearfield et al, ). In that longitudinal study of object exploration, low‐SES infants exhibited a reduction in the simple behaviour of mouthing across the first year but failed to replace that with other, more sophisticated exploratory behaviours, like rotating the object or transferring it from hand to hand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, higher SES infants made the optimal choice by utilizing the sound producing properties of the interaction object-surface ( . Importantly, low SES infants by the age of 12 months not only engage less in exploratory behavior but also exhibit less sophisticated behavior compared to high SES infants (Clearfield et al, 2014). The same study also reported that by 12 months, low SES infants exhibited less mouthing behavior, but in the mean time did not utilize any sophisticated exploratory behaviors (i.e.…”
Section: Page315supporting
confidence: 55%
“…Between the ages of 6, 9, and 12 months, infants from low-SES families demonstrated reduced overall levels of oral and manual object exploration (Clearfield et al 2014). Differences in early gesture production, known to predict later language learning (Rowe & Goldin-Meadow 2009a), also reflect SES disparities (Rowe & Goldin-Meadow 2009b).…”
Section: Prelinguistic Developmentmentioning
confidence: 99%